Crop Response to Interaction between Ethylene Sources and Nitrogen with Special Reference to Oilseed Crops - A.Lone1,K.A.Bhat2,S.M.Razvi2,S.A.Wani3, N.Wani2,S.Akhter2,S.Rashid4,N.H.Masoodi4,W.A.Payne, M.R.Mir1*,M.Mobin1,N.A.Khan1,M.A.Bhat2,N (Journal of Phytology, 2010)
Terrestrial plants assimilate approximately 1.4 gigatons of nitrogen annually and about 90 to 95% of the total in form of mineral nitrogen. Although more input of nitrogen increases growth and yield of the crops, but its excessive use causes environmental degradation phenomenon like eutrophication of the resources. Therefore, an approach is to be explored which minimizes the use of nitrogen without decreasing the growth and yield of crops. In this context, use of plant hormones may prove its potential as it has been found to enhance growth and productivity of the crop plants. It also improves the crop by manipulating source/sink relationship at pod development stage. Of several naturally occurring phytohormones, ethylene influences about all aspects of plant growth and development as well as the induction of some plant defence responses. Ethylene produced in trace amount elicits many physiological responses, acting at a concentration as low as 0.01ÂµL/L. Ethylene releasing compounds are applied to cereal crops to prevent lodging, thereby reducing yield losses and deterioration of grain quality and to mustard for increasing yield. Ethrel is versatile ethylene releasing agent have remarkable marketed value and registered for several crops. It is involved in a diverse array of cellular, developmental and stress-released processes in plants. Ethrel reduces the problem of pod shattering by restricting the flower and pod abortions. However in this study a number of examples of has been made to cover the aspects of interactions of nitrogen and ethrel (ethylene releaser) in the growth and development of plants are described; plant height, leaf area, leaf area index, dry weight, chlorophyll, photosynthesis, photosynthetically active radiation, ethylene evolution, nitrate reductase activity, nutrient accumulation, nitrogen uptake efficiency, nitrogen use efficiency and nitrogen utilization efficiency, seed yield, biological yield, harvest index, oil yield, oil content, acid value, iodine value and saponification. So the present study indicates that the process of growth and development in addition to the yield of plants is significantly affected by the ethrel along with basal nitrogen in both irrigated and non -irrigated conditions. Key words: Trichoderma spp., Drechslera tetramera, Biocontrol, Antagonism, Capsicum frutescens <span style="line-height: 110%; font-variant: normal !important; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-size: 7pt; font-weight: normal; mso-font-kerning: 0pt; mso-no-proof: no; mso-fareast-language: EN-SG; mso-ansi-language: EN-SG;" lang="EN-SG">M. R. Mir et al. Crop Response to Interaction between Ethylene Sources and Nitrogen with Special Reference to Oilseed Crops. J Phytol 2/10 (2010) 25-33